2014
DOI: 10.1542/peds.2014-0483
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Dental Caries in Children From Birth Through Age 5 Years: US Preventive Services Task Force Recommendation Statement

Abstract: DESCRIPTION: Update of the 2004 US Preventive Services Task Force (USPSTF) recommendation on prevention of dental caries in preschool-aged children. METHODS: The USPSTF reviewed the evidence on prevention of dental caries by primary care clinicians in children 5 years and younger, focusing on screening for caries, assessment of risk for future caries, and the effectiveness of various interventions that have possible benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
155
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(164 citation statements)
references
References 26 publications
1
155
0
4
Order By: Relevance
“…The American Academy of Pediatrics and the USPSTF recommend that physicians apply fluoride varnish as soon as the first tooth erupts on the basis of inferences from studies in dental practitioners. 11,40 Increasing the number of POHS visits per child is essential for promoting oral health because we observed a threshold effect of 4 visits. To prevent and control the development of caries until young children can more easily establish a dental home, NC Medicaid recommends delivery of POHS during already scheduled well-child visits at 6, 9, 12, 15, 18, 24, and 36 months.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The American Academy of Pediatrics and the USPSTF recommend that physicians apply fluoride varnish as soon as the first tooth erupts on the basis of inferences from studies in dental practitioners. 11,40 Increasing the number of POHS visits per child is essential for promoting oral health because we observed a threshold effect of 4 visits. To prevent and control the development of caries until young children can more easily establish a dental home, NC Medicaid recommends delivery of POHS during already scheduled well-child visits at 6, 9, 12, 15, 18, 24, and 36 months.…”
Section: Discussionmentioning
confidence: 78%
“…No trials have evaluated the effectiveness of parental counseling alone on oral health outcomes. 11,40 In its systematic review of dental caries prevention in children ,5 years of age, the USPSTF identified 2 studies in medical offices that included parental education as part of a multifaceted intervention, both of which showed beneficial results. 40 Among the different types of POHS provided, fluoride varnish has the strongest available evidence of a preventive effect for the primary dentition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Embora a dieta e a higiene bucal sejam os principais fatores associados ao desenvolvimento da doença (SHEIHAM;JAMES, 2015;PERES et al, 2016), outros fatores de risco contribuem para a alta prevalência, incluindo a baixa condição socioeconômica, pertencer a um grupo étnico minoritário, alto consumo de açúcares, uso inadequado de mamadeiras, defeitos de desenvolvimento do esmalte, baixo fluxo salivar, história prévia de cáries (pais, irmãos e a própria criança), falta de acesso a serviços odontológicos e falta de acesso a medidas preventivas (CONGIU et al, 2014;MOYER;FORCE, 2014;LIMA et al, 2016). Portanto, ações preventivas para a doença incluem estratégias educacionais, alimentação adequada, melhoria das condições socioeconômicas e melhoria das condições gerais de saúde, além do atendimento odontológico.…”
Section: Introductionunclassified